Operation room conflicts and management. - Khan , Bushra Alizah; Muhammad Arif; Memon , Ahson; Atif Sharjeel (International Journal of Endorsing Health Science Research, 2022)
Background: This study is based on management issues within the healthcare sector in Karachi. Specifically, it is focused on managing conflicts in the operation rooms, whereby team performance of Operation Theatre staff directly impacts patients' speedy recovery. Methodology: A quantitative survey was conducted involving the surgeons and Operation Theatre staff in Karachi's community hospitals. A closed-ended questionnaire was used in this study, and the questions mainly focused on the conflicts and management of doctors and staff in the operation theatre. Only those doctors and staff members included in the study who is currently working in the operation theatre division of the hospital. a Pearson correlation analysis was performed to assess the relationships between the factors affecting conflicts in the hospital's operating room. Results: The results indicated that the extent of conflict management is high. Factors include communication, leadership, training, adequate compensation, and role identification as perceived by employees. After performing OLS regression tests, the study found that the variable of miscommunication, the communication gap, plays a crucial role in accelerating disagreements of conflicts in Operation Theatre. Conclusion: A significant positive association between the factors and conflict management is observed. It suggests that operation theatre-related factors are improving with better conflict management practices.